Exploiting Petri Nets for Graphical Modelling of Electromagnetic Pulse Switching Operations. Issue 3 (7th December 2021) - Ventisei, Alessandro; Yakovlev, Alex; Pacheco‐Peña, Victor
Abstract: Most of the current computing technology relies on semiconductor‐based devices to perform fundamental switching/routing processes, however, recent advances in the field of optical computing have demonstrated that interconnected waveguides (in a series and/or parallel configuration) can enable high‐speed switching and routing of transverse electromagnetic (TEM) square pulses, creating new paradigms for alternative solutions in computing. In this work, a new approach for the modelling of TEM square pulse switching and routing in interconnected waveguides is proposed by unleashing the potential of Petri‐Nets (PNs). PNs are a highly regarded graphical modelling technique used in multiple scenarios ranging from industrial engineering, electronic circuits and even in chemical engineering for the study of chemical reactions. The fundamental principles of PNs along with their potential to graphically represent systems of equations are presented. These features are then exploited to represent the interaction of TEM square pulses in waveguide junctions using three or four interconnected waveguides (series and parallel configurations). This work represents a fundamental step toward allowing experts from multiple fields (such as computer science, electronics, and photonics) to contribute to the design of future computing systems by exploiting PNs in the design of electromagnetic wave‐based computing systems. Abstract : Petri Nets are exploited to model electromagnetic square pulses propagating through interconnected waveguides. Interaction of pulses in series and parallel configurations is studied demonstrating the potential for fast calculations and visual representation of pulse‐based switching processes. The technique could enable faster and more efficient design of electromagnetic pulse‐based computing devices.